Energy efficiency and optimization of convective hot air drying conditions of okra slices - Nwakuba, N.R.; Chukwuezie, O.C.; Asonye, G.U.; Asoegwu, S.N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
This paper presents the energy analysis and optimization of thin layer convective hot air drying conditions of okra slices in a hybrid solar-electric crop dryer based on the specific energy consumption and drying duration using response surface methodology (RSM). Fresh sliced okra samples (Abelmoschus esculentus) of 900g batch size were dried from initial to final desired moisture contents of 87.8 to 0.5% (wb) respectively. The Box-Behnken approach of Design Expert 7.0 statistical package was used to illustrate the effects of the varying levels of the drying parameters: drying air temperature (50, 60 and 70oC), air velocity (1, 1.5 and 2ms-1) and sample slice thickness (10, 15 and 20mm) on the drying duration and specific energy consumption of okra slices. All responses were fitted into a second order polynomial model and R2-values > 0.959 were observed in all treatment combinations. Suitability of the developed predictive response models was verified and validated with statistical analyses of the process parameters, experimental data, normal % probability plots, as well as simulated versus experimental data plots. Results obtained showed that the maximum and minimum mean energy consumptions were 69.02kWh and 2.02kWh, respectively. Regression models of specific energy consumption for each slice thickness were developed and their respective R2 compared. Thermal utilization efficiency of okra slices were in the range of 11.1 to 38.8%. The energy efficiency varied in the range of 11.2 to 45.6%; whereas the drying efficiency ranged between 28.1 and 49.6%. The desirability index technique was used to predict the optimum drying condition. The best drying conditions of 59.81oC, 2ms-1 and 10mm air temperature, air velocity and slice thickness, respectively were obtained. The corresponding predicted response values of 94.54mins and 3.54kWhg 1 were obtained for drying duration and specific energy consumption, respectively. The results from this study make available to food industries the optimized drying conditions for better quality dried okra slices as well as improve the dryer energy efficiency and reduce cost of drying operation.